Comparasion Model Analysis Time of Earthquake Occurrence in Indonesia based on Hazard Rate with Single Decrement Method - Novika, Fanny; Maulidi, Ikhsan; Marsanto, Budi; Amalina, Anvika Nur (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
The purpose of this studi is to find an expectations and variability as estimators of the risk of earthquakes occurring in each province in Indonesia. Indonesia is a country that prone to natural disasters, especially earthquakes and tsunamis. The earthquake disaster damage the buildings and casualties. The risk of loss from earthquakes can be transferred using insurance. Insurance companies certainly need an analysis to estimate the probability of an earthquake occurring at a certain location and time. Hazard rate has an important role in the prediction theory of the process of earthquakes. The hazard rate can be known by the single decrement method. After the hazard rate is known, the survival function and the distribution function of the cumulative distribution of earthquake data in Indonesia will be known to look for expectations and variability as estimators of the risk of earthquakes occurring in each province in Indonesia. The data used in this study is earthquake that happen in Indonesia categorized as destructive earthquake minimum 5 magnitude. We used the data to compare a hazard function using linear model, quadratic model, cubic model and exponential. First, we plot and then using each models find the standard error. The best model suggest for Indonesia prediction Time of Earthquake Occurrence using an exponential model.